The Effect Of Product Quality On Customer Loyalty At Waroeng Steak And Shake In Juanda Bekasi - Anissa Setyoningthias (International Journal of Education, Information Technology, and Others, 2022)
This study aims to determine whether there is an effect of product quality on customer loyalty at Waroeng Steak and Shake in Juanda Bekasi. The population in this study were customers of Waroeng Steak and Shake in Juanda Bekasi, totaling 400 people a week. The samples in this study were customers of Waroeng Steak and Shake taken using a random sampling of 80 people. The data analysis method uses a correlation technique with the Pearson Product Moment and Cronbach's Alpha formulas, and simple linear regression with the help of the SPSS program. The results of this study indicate that product quality as an independent variable has a direct positive effect on customer loyalty as the dependent variable, indicated by a regression value of 0.799%. Thus, the increase in Product Quality affects Customer Loyalty by 87.7%. While the remaining 12.3% is influenced by other variables that are not included in this research method